Power Relations in 2023 Merapi Eruption Management - Khuzaimah; Fransiscus Xaverius Sri Sadewo; Farid Pribadi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Local wisdom plays a crucial role in disaster mitigation, as exemplified during the 2023 eruption of Mount Merapi. Amid the eruption, societal myths circulated, asserting that Merapi erupted to conceal mining-induced holes. The statement was made by the Sultan of Yogyakarta Special District (Sultan DIY) during an interview with the media. It then receives responses and pros and cons from the community, then forms a community perspective. Researchers analyzed data from a Jogja TV interview with the Sultan, using semiotic analysis and Foucault's power relations theory. The findings reveal that there is discourse and knowledge that portrays Merapi's eruption as a corrective response to mining damage. This narrative gained societal acceptance, highlighting the influential role of local authorities in shaping disaster perceptions. However, the discourse also raises the counterpoint of disagreement.